Objective Structured Clinical Examination Case: Gina Babkins - Kevin Overbeck; Pamela Basehore; Anita Chopra (Association of American Medical Colleges, 2013)
Abstract Introduction The Gina Babkins case was developed at the University of Medicine and Dentistry of New Jersey's-School of Osteopathic Medicine (UMDNJ-SOM) as one of eight stations in the objective structured clinical examination (OSCE) for third-year medical students, during their geriatric clerkship rotation. The OSCE takes place in the final days of the clerkship, and counts towards a third of their final geriatric clerkship grade. Methods Successful execution of the standardized patient (SP) role required the SP to study and commit to memory the details of the patient's life and illness complaint. SPs were required to attend training sessions on a regular basis to ensure validity and reliability in case performance. The standardized patient playing Gina Babkins portrayed herself as a 75-year-old woman who presented to the outpatient office with a complaint of lightheadedness. She asked to be seen prior to her scheduled appointment because she was concerned about her lightheadedness. The examinee's task was to obtain a focused history, perform a focused physical examination, and counsel the patient regarding her situation. Following the encounter, the examinee documents the encounter in a subjective, objective, assessment and planning (SOAP)-style patient note. Results The case was used in both the 2010 and 2011 OSCE for third-year medical students, during their geriatric clerkship rotation at UMDNJ-SOM. In both OSCEs, no major pitfalls were reported. Discussion The purpose of the Gina Babkins encounter is to challenge students to manage a common geriatric presentation as part of an eight-station OSCE for third-year medical students completing a geriatric clerkship. Some helpful suggestions when carrying out this case are to make sure the SP has been trained well, has memorized their role, and that practice runs are conducted multiple times prior to the beginning of the usage of the case.